CALCULATION AND DESIGN OF A ROBUST SPEED CONTROLLER OF A FREQUENCY-CONTROLLED INDUCTION ELECTRIC DRIVE - N. J. Khlopenko (National Technical University "Kharkiv Polytechnic Institute", 2020)
Purpose. The aim of the work is the calculation and design of a robust speed controller of a frequency-controlled induction electric drive with parametric uncertainty and the presence of interferences in the feedback channel. Methodology. The calculation and design of the controller was carried out in four stages. At the first stage, a linearized mathematical model of the control object with parametric uncertainty was constructed and the transfer function of the H∞-suboptimal controller was calculated in the Robust Control Toolbox using the mixed sensitivity method. At the second stage, the stability of the robust system and the accuracy of stabilization of the induction machine speed with random variations of the object's and controller's uncertain parameters within the specified boundaries were explored. At the third stage, the influence of interferences arising in the feedback channel on the speed of the electric motor was explored in the Simulink package. At the final stage, the transfer function of the H∞-suboptimal controller was decomposed into a continued fraction using the Euclidean algorithm. This fraction was used to build the electric scheme of the controller. Results. Computer modelling of the transfer function of H∞-suboptimal controller, the robust stabilization system for the speed of the frequency-controlled electric drive with random variations of the uncertain parameters of the object and the controller at specified boundaries, as well as with the presence of varying intensity interferences in the feedback channel, was carried out. The choice of variable parameters was carried out according to the Monte-Carlo method. The curves of transient processes of the induction machine speed with parametric uncertainty and at different ranges of interference are constructed, as well as a Bode diagram for an open system. By the scatter of the obtained curves of the transient processes, the accuracy of speed stabilization of the machine was determined, and according to the Bode diagram, stability reserves in the amplitude and the phase of the robust system were determined. They are within tolerances with comparatively large deviations of the varied parameters and the range of interferences. Based on the investigations, an electrical circuit of the H∞-suboptimal robust controller was developed. Originality. The mathematical model has been developed and the methodology for calculating and designing of H∞-suboptimal robust speed controller of the frequency-controlled system of an induction electric drive with random variations of the uncertain parameters of the object and the controller at determined boundaries and the presence of interferences in the feedback channel, ensuring the stability of the system with allowable reserves of the amplitude and the phase and high accuracy of speed stabilization of the machine within the tolerances of uncertain system parameters and interferences was proposed. Practical value. The obtained structure of the controller from analog elements makes it possible to carry out modernization of the electric drives frequency-controlled systems in operation with minimal financial costs.